Fabrication of graphite grids via stencil lithography for highly sensitive motion sensors. (January 2016) - Park, Seong-Jun; Kim, Dae Woo; Jang, Sung Woo; Jin, Ming Liang; Kim, Seon Joon; Ok, Jong Min; Kim, Jong-Seon; Jung, Hee-Tae
Abstract: A graphite grid was fabricated using reactive ion etching with a stencil mask. The graphite film was synthesized through chemical vapor deposition on commercial Ni foil and was simply etched with a stencil mask using oxygen plasma during reactive ion etching. It had ∼85% optical transmittance at a 550-nm wavelength and ∼120 Ω/sq sheet resistance. Graphite grids placed on a human hand used to distinguish its motions showed high strain-sensing performance: its gauge factor ranged from 100 to 350, and its response times for strain loading and for release were short (10 and 80 ms, respectively). Because the graphite-based structures could be prepared in large quantities and because etching with a reusable stencil mask is very simple, mass production of high-performance motion sensors using the well-structured graphite grid is commercially feasible. Graphical abstract: